Uncovering the potential of CD44v/SYNE1/miR34a axis in salivary fluids of oral cancer patients. (15th February 2018) - Shah, Kavan; Patel, Shanaya; Modi, Bansri; Shah, Franky; Rawal, Rakesh
Abstract : Objectives: Late‐stage diagnosis is one of the major confounders for poor prognosis of patients with oral cancer owing to lack of a biomarker to diagnose this disease at an early stage. Moreover, till date, invasive biopsies are the only option to assess disease occurrence and progression in this malignancy. Thus, this study aims to identify and assess potential salivary markers in OSCC patients in order to open newer avenues in the field of non‐invasive biopsies. Methodology: Bioinformatic‐based analysis was performed to identify potential biomarkers that could be assessed in OSCC patients. The expression patterns of CD44v and its genetic and epigenetic modulators were assessed in saliva of OSCC patients, leukoplakia, and controls using real‐time and methylation‐specific PCR. Statistical analysis was conducted to understand the significance of these markers in terms of their clinical relevance. Results: CD44v/SYNE1/miR34a axis was identified using bioinformatic analysis, and the expression profile of these markers was assessed in saliva of OSCC patients. CD44v6 and CD44v10 demonstrated a significantly increased expression, whereas SYNE1 and miR34a depicted a significantly decreased expression in OSCC patients. Statistical analysis suggested a probable role of CD44v6, SYNE1, and miR34a in early stages of the malignancy, whereas a strong association was observed between CD44v6, CD44v10, and miR34a expression with locoregional aggressiveness and histopathological conditions. Conclusion: Collectively, these findings suggested a plausible role of CD44v/SYNE1/miR34a axis as non‐invasive salivary biomarkers to diagnose this disease at an early stage and predict the early onset of metastasis.